If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + 3 + 3b = 6 + -2b Reorder the terms: 3 + 2b + 3b = 6 + -2b Combine like terms: 2b + 3b = 5b 3 + 5b = 6 + -2b Solving 3 + 5b = 6 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. 3 + 5b + 2b = 6 + -2b + 2b Combine like terms: 5b + 2b = 7b 3 + 7b = 6 + -2b + 2b Combine like terms: -2b + 2b = 0 3 + 7b = 6 + 0 3 + 7b = 6 Add '-3' to each side of the equation. 3 + -3 + 7b = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 7b = 6 + -3 7b = 6 + -3 Combine like terms: 6 + -3 = 3 7b = 3 Divide each side by '7'. b = 0.4285714286 Simplifying b = 0.4285714286
| -2/9n=4/5 | | 2/5x=1/3 | | 100a^2-6=3 | | b-8=19 | | 2/5x=3/5 | | 2+x=3423423423 | | 3b+2=6b*3 | | 0=8n | | 98/7-9=5 | | -29.8r=59.6 | | 3x(5x+2)= | | f-4-3=-2 | | =3(2x-30) | | f-4-3=2 | | (M+5)+1.5=2 | | .44*7=x | | 15x+29(x-2)=294 | | o=v+1 | | 6x-24=-2x+32 | | (Y-4)+8=6 | | C+c=1 | | 6x-(24)=-2x+32 | | 6/4a+8+9/6a+12 | | 36.6y=256.2 | | 2log[3]+log[3]5=log[3](14x+3) | | (6x^5)(6)= | | (8x-16)=(4x+20) | | 16+5=15x | | d-2+5=-13 | | o+7=-3 | | 6b+18=8b-16 | | d-2+5=13 |